(Re)devenir Hui : l’ethnicisation d’une municipalité autonome à Baiqi (Fujian) - Pascale Bugnon (EchoGéo)
This article discusses the fluidity of ethnic categorization on the outskirts of the prefecture-level city of Quanzhou (Fujian province), where the Guo Han lineage has recently been recognized as Hui. This categorial transformation has involved the creation of an autonomous Hui municipality in 1990 and a new visibility of the “Muslimness” of this group. If the political role of ethnic categorization must be underlined, the Hui identity cannot be reduced to an invention of the State. By observing the worship practices of this lineage and the interethnic interactions with the Hui from the northwest, it is possible to understand the categorical plasticity of this ethnic group, made up of reappropriation and controversies.